Metabarcoding of mycetangia from the Dendroctonus frontalis species complex (Curculionidae: Scolytinae) reveals diverse and functionally redundant fungal assemblages - Vazquez-Ortiz, Karina; Pineda-Mendoza, Rosa María; González-Escobedo, Román; Davis, Thomas S.; Salazar, Kevin F.; Rivera-Orduña, Flor N.; Zúñiga, Gerardo (Frontiers in Microbiology, 2022)
Dendroctonus-bark beetles are associated with microbes that can detoxify terpenes, degrade complex molecules, supplement and recycle nutrients, fix nitrogen, produce semiochemicals, and regulate ecological interactions between microbes. Females of some Dendroctonus species harbor microbes in specialized organs called mycetangia; yet little is known about the microbial diversity contained in these structures. Here, we use metabarcoding to characterize mycetangial fungi from beetle species in the Dendroctonus frontalis complex, and analyze variation in biodiversity of microbial assemblages between beetle species. Overall fungal diversity was represented by 4 phyla, 13 classes, 25 orders, 39 families, and 48 genera, including 33 filamentous fungi, and 15 yeasts. The most abundant genera were Entomocorticium, Candida, Ophiostoma-Sporothrix, Ogataea, Nakazawaea, Yamadazyma, Ceratocystiopsis, Grosmannia-Leptographium, Absidia, and Cyberlindnera. Analysis of α-diversity indicated that fungal assemblages of D. vitei showed the highest richness and diversity, whereas those associated with D. brevicomis and D. barberi had the lowest richness and diversity, respectively. Analysis of β-diversity showed clear differentiation in the assemblages associated with D. adjunctus, D. barberi, and D. brevicomis, but not between closely related species, including D. frontalis and D. mesoamericanus and D. mexicanus and D. vitei. A core mycobiome was not statistically identified; however, the genus Ceratocystiopsis was shared among seven beetle species. Interpretation of a tanglegram suggests evolutionary congruence between fungal assemblages and species of the D. frontalis complex. The presence of different amplicon sequence variants (ASVs) of the same genus in assemblages from species of the D. frontalis complex outlines the complexity of molecular networks, with the most complex assemblages identified from D. vitei, D. mesoamericanus, D. adjunctus, and D. frontalis. Analysis of functional variation of fungal assemblages indicated multiple trophic groupings, symbiotroph/saprotroph guilds represented with the highest frequency (∼31% of identified genera). These findings improve our knowledge about the diversity of mycetangial communities in species of the D. frontalis complex and suggest that minimal apparently specific assemblages are maintained and regulated within mycetangia.